STRUCTURE OF THE KAZAKH FOLK-ACADEMIC INSTRUMENT — DOMBRA BASS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The transition from the oral form of music-making to the academic system, caused by the socio-historical events of the 20s of the last century, as is known, led to the creation of musical-educational and musical-cultural institutions in Kazakhstan. One of the first such famous musical groups in the republic was the Kazakh Folk Instruments Orchestra named after KazCEC (directed by A. Zhubanov), which was created in 1934 based on the Great Russian Folk Instruments Orchestra named after V.Andreyev. The expansion of its repertoire, which, along with Kazakh kuis and songs, began to include academic works by European, Russian and Soviet composers, put it before the need to reconstruct the instruments of the dombra group: transforming their diatonic system into chromatic; making their different timbres. The dombra bass instrument began to be made in Kazakhstan by local craftsmen, starting in 1935. Its reconstruction went through several historical stages. The body of this two-stringed plucked instrument, similar to the bass balalaika and domra of the orchestra of Russian folk instruments, was voluminous and was significantly larger than the size of the tenor dombra. Like the tuning of the latter, the bass dombra was two-stringed and tuned to a fourth (a-d). In the 1950s, it went through a second stage of reconstruction, when the nylon strings were replaced with metal ones, and one more string was added to the two. Accordingly, its tuning was also updated. In 1957-1958, the instruments of the Kurmangazy Orchestra were made in the Experimental Music Workshop at the Arts Committee under the Council of Ministers of the USSR.The material for this study was the bass dombra of 1959 (master K. Kasymov) and 1957 (master S. Fedotov). The article presents observations on the ergo-morphological features of the instruments.
Keywords: orchestra of Kazakh folk instruments, reconstruction, diatonic and chromatic scale, experimental music workshop